Philippine public administration as a field of study enduring and emerging areas, challenges and prospects - Ricote, Eleazar E.
Two distinguished scholars in 1986 eloquently affirmed the growth of Philippine Public Administration (PPA). Today, as the question lingers whether there is a Philippine Public Administration, the answer is a resounding "yes." The Philippine PA as a field of study and a profession has flourished over the years since its inception with a very rich collage of concerns, arenas, ideas and concepts. Mindful of the agenda encompassing the Philippine Public Administration, this article focuses on the emerging and existing subfields of the study. Specifically, the article showcases how instruction in PA has burgeoned all over the country, and highlight the most prominent and emerging fields of specialization of the Philippine PA instruction. This study concludes with a grateful insight that the Philippine PA has gone a long way beyond a mere imported field of inquiry into a highly evolved field of study that is particularly culture-bound, multi-disciplinary and eclectic.
Keywords: Association of Schools of Public Administration in the Philippines (ASPAP); Eastern regional organization for public administration (EROPA); Network of Asia-Pacific Schools and Institutes of Public Administration and Governance (NAPSIPAG); Public administration--Philippines.; Public administration--Study and teaching; Public administration--Study and teaching (Higher) Evaluation; Universities and colleges--Philippines.